THE EFFECT EXPOSURE OF BASYSPRINT UV-SETTER 850 AND DE-VELOPER TEMPERATURE ON DOT SIZE MANROLAND OFSET PRINTING PLATE - Muhammad Ari Yusroon (Kreator, 2021)
Abstract — Current development has led to the development of technology also, including the graphics industry, one of which is the offset printing platemaking process, which used to still use conventional methods in the process using film, the development growing currently into Computer to Plate (CtP) technology is used to be more efficient, better automation, and low cost run. This also affects the quality standard of the printed plate produced, one of quality on the printing plate is the dot/raster size that is produced according to digital data. CtP uses a linear standard within a tolerance 1% of dot recovery, but there are many factors that must be controlled in achieving this linear standard, some of these factors include the strength of exposure to CtP and the temperature of the developer. So in this study is to determine the combination of variables between the strength of CtP exposure with variables 5 ms/dot, 7 ms/dot, 10 ms/dot, 12 ms/dot and developer temperature with variables 18°C, 20°C, 22°C, 24°C which has the smallest overall average dot size shift in the highlights, midtones and shadows areas. The method used in this study is to measure the dot reference using a spectroplate on each variation of the variable combination of CtP exposure strength and developer temperature. Based on the research that has been done, it can be concluded that for the variable exposure power of 5 ms/dot with a temperature of 22°C is the variation that has the lowest average dot size shift with a shift of 1.8% for the highlights area, 1.5% for the midtones area, and 1.5% for the midtones area. 0.7% for the shadows area.